Paul Collins (ed.), Renewal and Resistance: Catholic Church Music from the 1850s to Vatican II (2010) - Schaefer, Edward (Journal of the Society for Musicology in Ireland, 2012)
A review of Paul Collins (ed.), Renewal and Resistance: Catholic Church Music from the 1850s to Vatican II (Bern: Peter Lang, 2010), ISBN 978-3-03911-381-1.